Apostasy and its implication in the entitlement to property on death - Mohd Salim, Wan Noraini (s.n, 2013)
Apostasy is quite a controversial issue in Malaysia though in Islam it is a criminal offence punishable with death penalty if the apostate does not repent within three days from the day he declared apostasy. For the apostate and some human rights activists including some Muslims themselves religion is a matter of choice and nobody can force anybody to remain a Muslim or to stop them from renouncing Islam